Evaluación de la capacidad de biotransformación de la sal sódica del ácido desoxicólico por actinomicetos. - Beltrán Ortiz, Jessica Alexandra (2015)
Actinomycetes are ubiquitous microorganisms in the soil, stagnant water, contaminated environments, etc. They are considered in the borderline between bacteria and fungi by their morphological and reproductive characteristics very similar to both groups of microorganisms. They are usually gram-positive and they are resistant to penicillin. Actinomycetes participate actively in the production of antibiotics and in the decomposition of animal and vegetable waste, therefore they were considered to study their ability to biotransform the sodium salt of bile acid deoxycholic to structures of industrial interest. Using chromatographic and magnetic resonance techniques, the biotransformative process has been followed. It was found the 3-keto-deoxycholic acid as a final product of the biotransformation. To identify the strain of actinomycetes, which had the higher biotransformation capacity of the sodium salt of deoxycholic acid, several techniques have been employed: Microgen tests, phenotypic characterization: morphological and kinetic characterization ando the cell size and, genotypic characterization: DNA extraction and molecular identification. The microorganism found was one of the gender Streptomyces. This investigation was part of the project "Aislamiento de Actinomicetos y su Capacidad para Degradar Estructuras Esteroideas" directed by Maria Elena Maldonado Ph.D. with the technical assistance of Valentina Veturi Ph.D.